Proteus: Virtualization for Diversified Tamper-Resistance - Anckaert, Bertrand; Jakubowski, Mariusz; Venkatesan, Ramarathnam (6th ACM Workshop on Digital Rights Management, 2006)
Despite huge efforts by software providers, software protection mechanisms are still broken on a regular basis. Due to the current distribution model, an attack against one copy of the software can be reused against any copy of the software. Diversity is an important tool to overcome this problem. It allows for renewable defenses in space, by giving every user a different copy, and renewable defenses in time when combined with tailored updates. This paper studies the possibilities and limitations of using virtualization to open a new set of opportunities to make diverse copies of a piece of software and to make individual copies more tamper-resistant. The performance impact is considerable and indicates that these techniques are best avoided in performance-critical parts of the code.